PENGEMBANGAN KONSEP KURSI BELAJAR UNTUK USIA PRA SEKOLAH (TK) - Utomo, Waskito; Budiastuti, Dyah (Industrial and Systems Engineering Assessment Journal (INASEA), 2004)
Learning chair for preschool in the market such as tends to payÂ less attention to physical condition or the size of children body, the function is not used optimally and the shape of the design is monoton, as well as uninteresting. The development of a learning chair hopefully can create conformity for user so that it can create the effective learning process, means the learning chairs not prevent the chlidren are to their activities. Therefor, a reserach on how to develop a learning chair product concept for preschool by paying attention to the aesthetic and ergonomic aspect is urgently conducted.